Effect of adhesive type and glue-line thickness on the fatigue strength of mortise and tenon furniture joints - Ratnasingam, Jegatheswaran; Ioras, Florin (Springer, 2013)
The fatigue strength of rectangular mortise and tenon rubberwood furniture joints made from polyvinyl-acetate (PVAc) and urea-formaldehyde (UF) adhesives were compared. The results showed that the allowable design stress for PVAc adhesive joints could be set at 30 % of its ultimate bending moment as compared to 25 % for the UF adhesive joint. Further, PVAc adhesive joints have large working tolerances for glue-line thicknesses which make it suitable for mass production furniture manufacturing.